BUILDING BRAND IN VIRTUAL MARKETING: MAINTAINING BUSINESS SUSTAINABILITY IN THE ERA OF COVID-19 - Endang Rudiatin; Tria Patrianti; Sugiatmi Sugiatmi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
In 4 years of observations of ISMEA (Indonesia Small Medium Enterprises Association), the research taken shows many SMEs neglect the effort to build a brand or branding then more focused on sales strategies to drive revenue instead. This condition will have an impact on the sustainability of the SMEs themselves. Since 2016, ISMEA is aggressively promoting SMEs products that are unique, homemade, and handmade through exhibitions and bazaars. From Exhibitions and Bazaars, the sales are much faster and definite rather than by stores or resellers. However, as a reaction to the impact of the Covid-19 pandemic, SMEs in ISMEA have to change their marketing method to Virtual Exhibitions. In virtual exhibitions, brand or branding plays a significant role in the business's reputation. Building a brand or branding is an effort to portray the image and perception that will be embedded in buyers or customers. The role of universities to educate about branding and reputation greatly assist SMEs on business sustainability in the era of Covid-19. Two months of training did conduct online and their products were sent to the trainers for evaluation and improvement. The SMEs were assigned tasks to enhance their skills. After the training, several SMEs began taking part in virtual marketing held such as BRI UMKM Virtual Mart, Ciputra Virtual Exhibition. In the future, ISMEA planned an initiative to organize its first virtual exhibition in October 2021 on Batik Day.